Core stability training for healthy athletes: A different paradigm for fitness professionals - Willardson, J. M. (Strength and Conditioning Journal, 2007)
Core stability exercises have become main stream, with rehabilitative methodologies now being applied to healthy athletes. A popular trend has been to perform resistance exercises on unstable equipment. However, resistance exercises performed on unstable equipment are not effective for the development of core strength and power due to the light loads, long tension times, and low velocities that characterize such lifts. Based on the current literature, performance of ground-based free weight movements might be better for the development of core strength and power due to the force, velocity, and core stabilizing requirements that are similar to the demands of sports skills.